The Mechanism of Acrylamide-Induced Neurotoxicity: Current Status and Future Perspectives - Zhao, Mengyao; Zhang, Boya; Deng, Linlin (Frontiers in Nutrition, 2022)
Acrylamide (ACR), a potential neurotoxin, is produced by the Maillard reaction between reducing sugars and free amino acids during food processing. Over the past decade, the neurotoxicity of ACR has caused increasing concern, prompting many related studies. This review summarized the relevant literature of recent years and discussed the exposure to occupational, environmental, and daily ACR contamination in food. Moreover, the metabolism of ACR and the potential mechanism of ACR-induced neurotoxicity were discussed, mainly including the axonal degeneration of the nervous system, nerve cell apoptosis, oxidative stress, inflammatory response, and gut-brain axis homeostasis. Additionally, the limitations of existing knowledge, as well as new perspectives, were examined, specifically regarding the connection between neurotoxicity caused by ACR and neurodegenerative diseases, NOD-like receptor protein 3 (NLRP3) inflammasome-related neuroinflammation, and microbiota-gut-brain axis signaling. This review might provide systematic information for developing an alternative pathway approach to assess ACR risk.